Applying a dimensional analysis method for implementing the gas hydrate technology when transporting and storing natural gas - Pedchenko, Larysa; Pedchenko, Nazar; Pedchenko, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is the process parameters for the forced conservation of gas hydrate by a layer of ice to ensure its stability under non-equilibrium conditions. These conditions are atmospheric pressure and a slight negative temperature. However, the application of water in the liquid phase and its subsequent crystallization, with the release of a corresponding amount of process energy, is accompanied by the dissociation of the surface layer of gas hydrate, and therefore the loss of gas. A decrease in the melting level of gas hydrate could be achieved by increasing the cooling level of gas hydrate structures. However, this increases the operating costs of the technology. This paper proposes a variant for substantiating the process parameters for the forced conservation of natural gas hydrate structures. To this end, by using the dimensionality analysis method, dimensionless complexes were established: Fourier criterion (Fo); criterion characterizing the relative thermal conductivity of bodies (Kε), Kosovich criterion (Ko), dimensionless temperature criterion Θ1/Θ0 and the criterion equation. The coefficient and degrees of dimensionless complexes in the criterion equation were experimentally determined. They make it possible to describe the process of forced conservation of gas hydrate structures regardless of size and shape. The application of dimensionless dependences and criterion equations could make it possible to determine in a simplified form parameters for the technological process of industrial production of gas hydrate structures with the required properties (stability during transportation and storage under non-equilibrium thermobaric conditions without gas loss). Based on experimental studies, the limits of the applied parameters of the stability of gas hydrate structures under non-equilibrium conditions have been established. For them, the criterion of dimensionless temperature Θ1/Θ0 is within 0.02–0.04